(untitled) (International Journal of Environmental Sciences, 2025)
Despite existing safety protocols, many organizations experience gaps in fire emergency preparedness, particularly among frontline security personnel who are often the first responders during fire incidents. Previous incidents have highlighted issues such as delayed response, inadequate coordination, and limited emergency skills among security teams, reflecting a need for systematic evaluation of preparedness factors. This study aims to identify and validate the underlying dimensions influencing the preparedness of security personnel in responding to fire emergencies during drills. Data were collected from 445 respondents across various organizational settings using a random sampling method to ensure representativeness and reduce selection bias. Analysis was conducted using Exploratory Factor Analysis (EFA) via Principal Component Analysis (PCA) with Varimax rotation. The data analysis revealed eleven (11) core constructs comprising 54 validated items with factor loadings exceeding the threshold and communalities greater than 0.30. These constructs are Emergency Preparedness on Planning, Fire Protection System, Fire Risk Reduction, Incident Command System & ERT, Leadership, Communication in Fire Emergency, Fire Emergency Training, Awareness and Education, Responders’ Emergency Response Capabilities, Organizational Commitment, and Effectiveness of Fire Drill Preparedness. Each construct contains 4 to 6 items, collectively capturing behavioral, procedural, and organizational aspects of fire emergency readiness. The findings underscore the multifaceted nature of emergency preparedness and provide a robust empirical basis for developing a comprehensive and structured fire emergency management framework tailored for security personnel in the workplace. These validated dimensions can inform policy, training, and operational strategies to enhance organizational resilience and response efficacy.